Perception towards Cultured Meat: A Survey of Potential Consumers in India - P S, Girish; Kacham, Santhosh; D C, Praneetha; Rao, Madhusudan; V, Bhaskar; Ramakrishna, C; Raja, Balamanikandan (Journal of Meat Science, 2024)
Meat is an important component of the food basket of India and  it plays a critical role in meeting protein demand and ensuring the  nutritional security of the ever-growing population. Concerns related to  environmental impact, shrinking resources, and animal welfare issues  continue to haunt the meat industry. Cultured meat on the other hand  promises to produce meat without the need to rear the livestock by  utilizing fewer resources with minimum impact on the environment.  Here, an effort has been made to capture the perception of Indian  consumers towards cultured meat by conducting a survey. Results of  the survey revealed that about 60.52% of the respondents are willing  to buy the cultured meat if made available. It was found that 45.9%  of the respondents who are willing to buy cultured meat are ready to  pay a premium price range between 10-30%. Among the respondents,  54.0, 59.1 and 66.5% opinedthat cultured meat is a potential alternative  to traditional meat in view of challenges like sustainability, nutritional  security, and animal welfare, respectively.
Keywords: Cultured meat; Consumer perception; India; Consumer research; Survey